Alla ricerca di un ‘altro’, un ‘vero’, Calvino - Musarra-Schrøder, Ulla (Incontri. Rivista europea di studi italiani, 2022)
Review of: A. Baldi, The Author in Criticism. Calvino's Authorial Image in Italy, the United States, and the United Kingdom, Fairleigh Dickinson University Press, 2020, p. 296, ISBN 9781683931911, € 114.55.